Human face detector: an enhancement of eigenfaces and gaussian pyramid-based human face detection algorithm - Mary Ann Gualas an Janairo Jiao. 4 0 16; 5
u
Undergraduate Thesis: (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2